MANAJEMEN PEMASARAN BISNIS SYARIAH BAGI USAHA MIKRO KECIL DAN MENENGAH DESA CINANGNENG, KECAMATAN TENJOLAYA, KABUPATEN BOGOR - Tubagus Rifqy Thantawi; Mohamad Kharis Mubarok; Muhamad Yogi Adrian (Jurnal Pengabdian Kepada Masyarakat Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2022)
The purpose of this community service is to provide provisions for micro, small and medium enterprises in Cingneng Village so that they have the skills and knowledge in developing skills in digital-based sharia marketing practices. Activities carried out are in the form of interactive discussions with micro, small and medium enterprises (MSMEs) in Cinangneng Village to find solutions together by introducing modern sharia marketing methods that are easy to understand and easy to use by Cinangneng Village MSMEs, as an effort to improve income. The output target of this community service program is to increase awareness for the people in Cingneng Village, Tenjolaya District, Bogor Regency. With qualified knowledge related to modern sharia marketing, it is hoped that the UMKM actors in Cinangneng Village will have the characteristics of a formidable entrepreneur and are ready to compete as well as compete in global business competition and be able to understand digital-based sharia marketing methods.